Implementasi Rapid Assessment Bio Psiko Sosial-Daily Living Berbasis Komunitas Dalam Penanganan Bencana Di Desa Gasol Kecamatan Cugenang Kabupaten Cianjur - Atma, Annisa Nur; Favourita, Lina; Mildawati, Milly (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
In disaster management, it is very important to involve fast and organized steps in responding to the needs of survivors so that they can be immediately handled with data on the location of the incident and the affected area within 24 (twenty four) hours. One of them is a rapid assessment or Rapid Assessment, where in the disaster assessment cycle, a rapid assessment is carried out at the earliest when a disaster occurs. This research was carried out to develop a rapid assessment format so that it can be used practically by communities in disaster-prone environments according to the characteristics of the residents and their area as well as strengthening community participation in disaster management. The research subjects were the people of Gasol Village who were members of the Cugenang District Disaster Preparedness Team, Cianjur Regency using Participatory Action Research (PAR) techniques. Research was carried out by conducting interviews, observations, documentation studies and FGD (Focus Group Discussion). In the form that has been prepared with the community, for the client's internal side and also the client's relationship with his environment, BPS (Bio Psycho Social) and DL (Daily Living) assessments are included. So the expected results from the BPS-DL rapid assessment engineering also aim to speed up the distribution of aid and decision making for related parties, especially Gasol Village.